An Empirical Study of Knowledge Sharing in Agile Organisations: An Indian Perspective - Kaur, R; Sidhu, B.K (International Journal of Computer Sciences and Engineering, 2018)
Knowledge is a core resource for agile organizations and sharing of knowledge is essential across any organization. Within teams, different members often have different deep knowledge and knowledge management is required in every software industry. This paper empirically investigates the knowledge sharing environment in the context of agile methodologies from software practitioners in India. This paper can serve as a reference to the agile users who tends to initiate knowledge sharing culture in the organisation. Organisations are divided into small, medium and large size based upon the total number of teams in the company using agile methodology. It is found that the communication-related issues are the major concern for effective knowledge sharing in the Indian software industry. Knowledge sharing through review meetings and the scrum of scrums are the most used practice among all respondents whereas informal meeting is the least accepted practice for knowledge transfer. We also employed cross table analysis to evaluate the association among practices adopted, issues faced for effective KS and company experience on agile software development.